PERLINDUNGAN HUKUM TERHADAP KURATOR DALAM MENJALANKAN TUGAS DEMI KEPENTINGAN HARTA PAILIT DENGAN MELAKUKAN GUGATAN ACTIO PAULIANA (STUDI PUTUSAN PRAPERADILAN NOMOR 89/PID/PRAP/2016/PN.JKT.SEL): Larmi Kristiani - admin, admin; Hariz Hamdallah, Muhammad Andika (Reformasi Hukum, 2018)
The curator is a party appointed by law through the decision of the Panel of Judges of the Commercial Court at the District Court in a bankruptcy case to administer bankrupt assets. In Law Number 37 of 2004 concerning Bankruptcy and PKPU, the Curator is in charge as far as possible to add the debtor's bankrupt assets to the benefit of Creditors, but in carrying out these duties, the Curator can be criminalized by the Creditors and the Debtor itself. The Bankruptcy Law and PKPU have not provided guarantees of legal certainty and protection for curators when carrying out their duties. This study aims to examine the legal protection of curators who carry out their duties in the interests of bankrupt assets by filing a lawsuit actio pauliana and to find out and assess the legal risk if the actio pauliana lawsuit results in the criminalization of curators (Study of Pre-Court Decision Number 89 / Pid / Prap / 2016 / PN.Jkt.Sel). This research method is normative juridical. The conclusion of the study shows that: 1. The law provides protection to the Curator through Article 50 of the Criminal Code, namely that anyone who commits an act to implement the provisions of the law, is not convicted. Article 16 of Law Number 18 Year 2003 concerning Advocates, because the Curator is also an Advocate, states that advocates cannot be prosecuted both in civil and criminal manner in carrying out their professional duties in good faith for the benefit of client defense inside and outside the court session. This is in accordance with the right of judicial review of the provisions of Article 16 of the Law on Advocates in the decision number 26 / PUU-XI / 2013. Article 16 of the Advocate Law contradicts the 1945 Constitution and does not have binding legal force insofar as it is not interpreted, advocates cannot be prosecuted either in civil or criminal manner in carrying out their professional duties in good faith for the benefit of client defense inside and outside the court session. With this provision, actually the legal protection has been obtained by the Curator who is actually an Advocate. Types of legal protection are repressive legal protection aimed at resolving disputes. Efforts to obtain legal protection were carried out by the PT Metro Batavia Curator Team by submitting a pretrial application registered with Number 89 / Pid / Prap / 2016 / PN.JKT.SEL. 2. In connection with this task, the Curator Team filed an Actio Pauliana lawsuit against Yudiawan Tansari. Of course without risk and one proof of the risk with the claim of actio pauliana, is that the Curator Team was made a suspect because it was considered to violate Article 263 of the Criminal Code.